Belief crisis as the tendency of development of culture of new time - l.V. Topchiy (Advanced Engineering Research)
In article is considered a problem of crisis of religious belief in the West European culture, the factors which have caused it - scientific revolution and philosophical concepts of New time, and also its display in art sphere.